2012
DOI: 10.4161/cam.18702
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of integrin function by divalent cations

Abstract: Integrins are a family of α/β heterodimeric adhesion metalloprotein receptors and their functions are highly dependent on and regulated by different divalent cations. Recently advanced studies have revolutionized our perception of integrin metal ion-binding sites and their specific functions. Ligand binding to integrins is bridged by a divalent cation bound at the MIDAS motif on top of either α I domain in I domain-containing integrins or β I domain in α I domain-less integrins. The MIDAS motif in β I domain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
175
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(188 citation statements)
references
References 105 publications
(203 reference statements)
11
175
0
2
Order By: Relevance
“…To determine whether intracellular tension is needed to maintain myofibril alignment, we incubated patterned hPSC-CMs in EDTA to chelate calcium and reduce integrin-mediated cell-substrate adhesion (33,34) and disrupt myofibril tension (35) and the intracellular balance of forces. Beating stopped upon EDTA addition, whereas buckling, disruption, and loosening of myofibrils and loss of sarcomere periodic organization increased with incubation (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether intracellular tension is needed to maintain myofibril alignment, we incubated patterned hPSC-CMs in EDTA to chelate calcium and reduce integrin-mediated cell-substrate adhesion (33,34) and disrupt myofibril tension (35) and the intracellular balance of forces. Beating stopped upon EDTA addition, whereas buckling, disruption, and loosening of myofibrils and loss of sarcomere periodic organization increased with incubation (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This difference could be attributed to the fact that the mechanisms of integrin activation induced by Mn 2ϩ and talin/PMA are different. Mn 2ϩ activates integrins by direct binding to the metal ion binding sites in the ␤I domain, which triggered integrin activation independently of cytoplasmic signaling (19,42,43), whereas talin or PMA activate integrin via inside-out signaling by regulating the binding of intracellular effector molecules to integrin cytoplasmic domains, which triggers the global conformational rearrangement and activation of integrin (15,17,18,33,34). In addition, FRET analysis of the distance between the integrin head domain and the cell membrane in this study also demonstrated that integrin ␣ 4 ␤ 7 stimulated by PMA or overexpression of talin were less extended than Mn 2ϩ -activated ␣ 4 ␤ 7 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several intracellular effector molecules, such as talin and kindlins, have been shown to activate integrin through the interaction with integrin cytoplasmic domains (15)(16)(17)(18). In addition to inside-out signaling, extracellular metal ions can also regulate adhesion by integrins (19 or removal of Ca 2ϩ strikingly increases the affinity and adhesiveness of almost all integrins (20 -22). Studies have shown that integrin affinity is regulated by divalent cations via a cluster of three divalent cation-binding sites in the integrin ␤ 7 I domain, with the metal ion-dependent adhesion site (MIDAS) at the center and flanked by the synergistic metal ion-binding site and the adjacent to MIDAS (10,11,19,(23)(24)(25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also reported that distinct kindlin-3 binding patterns can lead to distinct binding affinities of mucosal vascular addressin cell adhesion molecule-1 and VCAM-1 to integrin ␣4␤7 (18). In addition to inside-out signaling, extracellular metal ions can also regulate integrin affinity via a cluster of three divalent cation-binding sites in integrin ␤ I domain (19). Compared with the low affinity state in Ca 2ϩ /Mg 2ϩ , addition of Mn 2ϩ or removal of Ca 2ϩ strikingly increases the affinity and adhesiveness of almost all integrins (20 -22).…”
mentioning
confidence: 99%